TREN FENOMENA âPisiDiâ (Pikun Usia Dini) SEBAGAI DUGAAN AWAL GEJALA DEMENSIA DI KOTA MALANG - Tantomi, Achmad Iwan; Baabdullah, Abdurrachman Omar; Sagita, Andri (Program Kreativitas Mahasiswa - Penelitian, 2013)
The incidence and prevalence of dementia in Indonesia hasnât been precisely determined yet, especially in Malang city. The purpose of this study is to identify the prevalence of âPisiDiâ phenomenon as the early symtoms of dementia with Clock Drawing Test. The study design was Observational Analitical with cross-sectional method. The âPisiDiâ phenomenon could be indicated as the early symptom of dementia. The prevalence of respondents with early symptom of dementia was (12%) for group I and II, III (23%), IV (26%), and V (27%) in Malang City. The highest rate were obtained at Lowokwaru district (28%) equals with 34 people. Keywords: Early Age Senility, Early Symptoms of Dementia